Analisis kemampuan berpikir kritis peserta didik dalam menemukan ide pokok teks non fiksi deskripsi kelas IV sekolah dasar - Maura, D S; Rukayah, Rukayah; Saputri, D Y; Bakdiyah, N (Universitas Sebelas Maret, 2021)
This research was undertaken to analyze of critical thinking skills in finding the main idea of a nonfiction descriptive text of IVth grade students in SDN Bratan 1 No. 71 in the academic year of 2021/2022. Critical thinking skill emphasizes of ability to understanding the question, to make a reason based on fact to make a conclusion, using the information to problem solving to give a verification, and to evaluate their final result. Critical thinking skill are needed for students to dealing some real life problems in the 21th century. This research uses descriptive qualitative research methods. The subjects of this research were teachers and students of IV.Bth grade in SDN Bratan 1 No. 71 in academic year 2021/2022. The data collection techniques used include test, interviews, and documentation with data validation used triangulation technique. The data analysis used Miles-Huberman’s interactive analysis model. This data analysis consists of four main components such as data collection, data reduction, data presentation, and conclusions. The results of this research shows that the analysis of critical thinking skill at SDN Bratan 1 No. 71 is in the critical enough criteria. The percentages of the analysis of critical thinking skill of IV.Bth grade in SDN Bratan 1 No. 71. This is the percantages for each indikator. The percentage at the focus obtained is 43%. And the indicator of reason obtained is 57%. And in the inference indikator obtained is 21,4%. And in the situation indicator obtained is 14,3%. And in the clarity indicator obtained is 14,3%. And in the overview indicator obtained is 42,8%. The most dominant indicator is focus, reason, and overview